Hak Asasi Manusia dalam Sistem Politik Indonesia: Antara Konstitusi dan Realitas - Fauziah Indriani; Putri Athena Maharani Tanu; Shakila Ayu Dwi Lestari; Stevani Anekhe Dwinita Karo (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
Human rights in the Indonesian political context show a discrepancy between the principles set out in the constitution and their implementation on the ground. While the Indonesian constitution guarantees fundamental rights, various institutional, political and cultural barriers often prevent their effective implementation. This research investigates the dynamics of human rights in the Indonesian political system, highlighting the gap between constitutional norms and their application in practice. Through the analysis of various legal documents and human rights case studies, this article identifies key challenges in the enforcement of human rights in Indonesia. The main results show that while Indonesia's constitution clearly guarantees a range of human rights, there are institutional, political and cultural barriers that hinder the implementation of these rights. The article provides policy recommendations to strengthen human rights protection, including legal reform and capacity building of law enforcement agencies. It discusses the protection of human rights in the Indonesian constitution, its implementation in political practice, as well as cases of violations that have occurred. The Indonesian Constitution guarantees human rights through various provisions listed in the 1945 Constitution, including civil, political, economic, social and cultural rights. However, the implementation of human rights in political practice often faces challenges, including corruption, abuse of power, and discriminatory policies. Various cases of human rights violations, such as arbitrary arrests, violence against minorities, and labor rights violations, show the gap between law and practice. Various parties, including the government, non-governmental organizations, civil society, and the international community, play an important role in protecting and promoting human rights in Indonesia. Effective cooperation between these various parties is needed to ensure respect and protection of human rights in all aspects of national life.